2010
DOI: 10.1090/s0002-9939-10-10246-9
|View full text |Cite
|
Sign up to set email alerts
|

Resolvable maps preserve complete metrizability

Abstract: Abstract. Let X be a Polish space, let Y be a separable metrizable space, and let f : X → Y be a continuous surjection. We prove that if the image under f of every open set or every closed set is resolvable, then Y is Polish. This generalizes similar results by Sierpiński, Vainštain, and Ostrovsky.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For α= 1 (X is an abs. G δ -set), the conclusion follows from the recent results of S. Gao and V. Kieftenbeld [2], P. Holicky and R. Pol [3], and hence Y is an abs. Borel sets of the same class α.…”
Section: Preservation Of Borel Classes By Clopen-lc Functions In Thementioning
confidence: 60%
“…For α= 1 (X is an abs. G δ -set), the conclusion follows from the recent results of S. Gao and V. Kieftenbeld [2], P. Holicky and R. Pol [3], and hence Y is an abs. Borel sets of the same class α.…”
Section: Preservation Of Borel Classes By Clopen-lc Functions In Thementioning
confidence: 60%
“…The motivation for both papers was to solve a question by A. Ostrovsky posed in [9]. Let us point out that we were informed by Su Gao that he and Vincent Kieftenbeld answered the Ostrovsky question independently in [2]. Their method is different from our one.…”
Section: Introductionmentioning
confidence: 93%
“…Let f : Q → D be a one-to-one mapping of the space Q of rational numbers onto the countable discrete space D. Clearly, f is piecewise continuous and ∆ 0 2 -measurable. Gao and Kientenbeld [GK,Proposition 4] got a characterization of nonresolvable subsets of Q. In particular, they showed that there exists a nonresolvable subset…”
mentioning
confidence: 99%